Comparison of tribological performances of sulfur based and boron succuminide containing antiwear additive with ZDDP by engine bench tests. Issue 4 (13th June 2016) - Özkan, Doğuş; Yağci, M. Barış; Birer, Özgür; Kaleli, Hakan
Abstract : Purpose: This study aims to evaluate and compare by 100 hours engine bench tests the tribological performances of two types of lubrication oils, which were sulfur-based, boron succinimide-containing antiwear package (NP-3) oil and conventional zinc dialkyldithiophosphate (ZDDP)-containing (R-1) oil. Design/methodology/approach: The tribological performances of the oils were evaluated in three main contexts, including engine tests, physical/chemical changes and surface analysis. Findings: Results showed that NP-3 lubrication oil, which was environment- and catalyst-friendly, can be an alternative lubrication oil with its tribological performance due to similar antiwear characteristics with the ZDDP. Originality/value: Attempts to develop catalysis- and environment-friendly antiwear additive packages have not presented popular or commonly used ZDDP-free products for the vehicle industry. This study presents tribological characterization of a newly developed ZDDP-free lubricating oil by engine bench tests.